A New Calmodulin-Binding Protein Expresses in the Context of Secondary Cell Wall Biosynthesis and Impacts Biomass Properties in Populus - Badmi, Raghuram; Payyavula, Raja S.; Bali, Garima; Guo, Hao-Bo; Jawdy, Sara S.; Gunter, Lee E.; Yang, Xiaohan; Winkeler, Kimberly A.; Collins, Cassandra; Rottmann, William H.; Yee, Kelsey; Rodriguez, Miguel; et al. (Frontiers in Plant Science, 2018)
A greater understanding of biosynthesis, signaling and regulatory pathways involved in determining stem growth and secondary cell wall chemistry is important for enabling pathway engineering and genetic optimization of biomass properties. The present study describes a new functional role of PdIQD10, a Populus gene belonging to the IQ67-Domain1 family of IQD genes, in impacting biomass formation and chemistry. Expression studies showed that PdIQD10 has enhanced expression in developing xylem and tension-stressed tissues in Populus deltoides. Molecular dynamics simulation and yeast two-hybrid interaction experiments suggest interactions with two calmodulin proteins, CaM247 and CaM014, supporting the sequence-predicted functional role of the PdIQD10 as a calmodulin-binding protein. PdIQD10 was found to interact with specific Populus isoforms of the Kinesin Light Chain protein family, shown previously to function as microtubule-guided, cargo binding and delivery proteins in Arabidopsis. Subcellular localization studies showed that PdIQD10 localizes in the nucleus and plasma membrane regions. Promoter-binding assays suggest that a known master transcriptional regulator of secondary cell wall biosynthesis (PdWND1B) may be upstream of an HD-ZIP III gene that is in turn upstream of PdIQD10 gene in the transcriptional network. RNAi-mediated downregulation of PdIQD10 expression resulted in plants with altered biomass properties including higher cellulose, wall glucose content and greater biomass quantity. These results present evidence in support of a new functional role for an IQD gene family member, PdIQD10, in secondary cell wall biosynthesis and biomass formation in Populus.